Iron-Dependent Mitochondrial Dysfunction Contributes to the Pathogenesis of Pulmonary Fibrosis - Takahashi, Mai; Mizumura, Kenji; Gon, Yasuhiro; Shimizu, Tetsuo; Kozu, Yutaka; Shikano, Sotaro; Iida, Yuko; Hikichi, Mari; Okamoto, Shinichi; Tsuya, Kota; Fukuda, Asami; Yamada, Shiho; et al. (Frontiers in Pharmacology, 2022)
Although the pathogenesis of pulmonary fibrosis remains unclear, it is known to involve epithelial injury and epithelial-mesenchymal transformation (EMT) as a consequence of cigarette smoke (CS) exposure. Moreover, smoking deposits iron in the mitochondria of alveolar epithelial cells. Iron overload in mitochondria causes the Fenton reaction, leading to reactive oxygen species (ROS) production, and ROS leakage from the mitochondria induces cell injury and inflammation in the lungs. Nevertheless, the mechanisms underlying iron metabolism and pulmonary fibrosis are yet to be elucidated. In this study, we aimed to determine whether iron metabolism and mitochondrial dysfunction are involved in the pathogenesis of pulmonary fibrosis. We demonstrated that administration of the iron chelator deferoxamine (DFO) reduced CS-induced pulmonary epithelial cell death, mitochondrial ROS production, and mitochondrial DNA release. Notably, CS-induced cell death was reduced by the administration of an inhibitor targeting ferroptosis, a unique iron-dependent form of non-apoptotic cell death. TGF-β-induced EMT of pulmonary epithelial cells was also reduced by DFO. The preservation of mitochondrial function reduced TGF-β-induced EMT. Furthermore, transbronchial iron chelation ameliorated bleomycin-induced pulmonary fibrosis and leukocyte migration in a murine model. Our findings indicate that iron metabolism and mitochondrial dysfunction are involved in the pathogenesis of pulmonary fibrosis. Thus, they may be leveraged as new therapeutic targets for pulmonary fibrosis.